Surgical lymph node assessment influences adjuvant therapy in clinically apparent stage I endometrioid endometrial carcinoma, meeting Mayo criteria for lymphadenectomy. Issue 5 (16th February 2021) - Pendlebury, Adam; Radeva, Milena; Rose, Peter G.
Abstract: Objective: To evaluate the impact of surgical lymph node assessment for clinically apparent, stage I endometrioid endometrial adenocarcinoma meeting Mayo criteria for lymphadenectomy. Methods: Patients with endometrioid endometrial adenocarcinoma meeting Mayo criteria for lymphadenectomy who underwent hysterectomy and lymphadenectomy were identified. Algorithms for adjuvant therapy with and without lymphadenectomy were developed utilizing NCCN guidelines, PORTEC 1, and PORTEC 2. Patients served as their own control to determine the frequency of treatment modification. Results: A total of 357 patients were analyzed. Using our algorithms treatment modification would have occurred because of lymphadenectomy in 62.8% of patients if whole pelvic external beam radiation was used for patients meeting inclusion criteria for PORTEC 1. Treatment modification would have occurred in 16.2% of patients if vaginal brachytherapy was used for patients meeting the inclusion criteria for PORTEC 2. Of the total, 53.8% of patients meeting inclusion criteria for PORTEC 1 would have had a reduction in adjuvant therapy from whole pelvic radiotherapy to vaginal brachytherapy alone. Only 9.0% of patients would have adjuvant therapy increased to include external beam radiotherapy and chemotherapy based on the presence of positive lymph nodes. Conclusions: Applying standard adjuvant treatment algorithms to real patient data, surgical lymph node assessment appears to frequently alter treatment allocation.